Polymers Made by Inverse Vulcanization for Use as Mercury Sorbents - Chalker, Justin M.; Mann, Maximilian; Worthington, Max J. H.; Esdaile, Louisa J. (Organic Materials, 2021)
Inverse vulcanization is a process in which highly abundant and low-cost elemental sulfur is copolymerized with an unsaturated organic molecule such as a polyene. This process has provided a variety of useful materials with high sulfur content—typically 50% or greater in sulfur by mass. These materials have garnered increasing interest in research as sorbents for mercury, due to the high affinity of sulfur for mercury. In this review, the features of mercury sorbents made by inverse vulcanization are presented. Additionally, case studies are provided to illustrate the variety of polymer architectures accessible with this chemistry, the versatility of these materials in mercury remediation, and prospects for industrial use.1 Introduction2 Sulfur Polymers by Inverse Vulcanization3 Sulfur Polymers as Mercury Sorbents4 Increasing Surface Area to Improve Mercury Uptake5 Crosslinker Considerations6 Sorption of Different Forms of Mercury7 Life-Cycle Management8 Conclusions and Outlook
Keywords: inverse vulcanization; mercury; polysulfides; sulfur; sulfur polymers